Challenges of Online Medical Education in Pakistan During COVID-19 Pandemic - Farooq, Fareeha; Rathore, Farooq Azam; Mansoor, Sahibzada Nasir (Journal of the College of Physicians and Surgeons--Pakistan, 2020)
The novel coronavirus (COVID-19) pandemic has adversely affected economy, social life, and educational services all around the globe. Medical colleges and universities are facing challenges to provide quality education to their students during this prolonged period of lockdown. Technologically advanced countries have systems in place for e-learning and online medical education. This is not the case with most of the low-income countries like Pakistan. Here, we describe the challenges being faced by medical faculty members and students in Pakistan while engaging in online medical education during the COVID-19 pandemic. These include lack of faculty training and institutional support, internet connectivity issues, maintaining student engagement, online assessments, and problems with understanding the unique dynamics of online education. A collaborative approach involving all stakeholders, intuitional support, use of free online training resources, and out of box thinking can help overcome these challenges. Key Words: Analysis, E-learning, Coronavirus, Developing countries, Solutions.The novel coronavirus (COVID-19) pandemic has adversely affected economy, social life, and educational services all around the globe. Medical colleges and universities are facing challenges to provide quality education to their students during this prolonged period of lockdown. Technologically advanced countries have systems in place for e-learning and online medical education. This is not the case with most of the low-income countries like Pakistan. Here, we describe the challenges being faced by medical faculty members and students in Pakistan while engaging in online medical education during the COVID-19 pandemic. These include lack of faculty training and institutional support, internet connectivity issues, maintaining student engagement, online assessments, and problems with understanding the unique dynamics of online education. A collaborative approach involving all stakeholders, intuitional support, use of free online training resources, and out of box thinking can help overcome these challenges. Key Words: Analysis, E-learning, Coronavirus, Developing countries, Solutions.